(3GdEQTGO GdfaSj aj eQMdI GdMVGfI (B/s - (3Ndjd, QSejI Ydjs ((3GdbGgQI(B:s (3ecJHI hgHI ,s (3OGQ ZQjH,s, 1980)
(3jJfGhd cJGH (B((3GdEQTGO GdfaSj aj eQMdI GdMVGfI(B) (3hGdPj bGe HJCdjag (B((3QSejI Ydj Ndjd(B) (3aj MhGdj (B(158) (3UaMI ef GdbWY GdeJhSW ehVhY (B((3GdEQTGO GdfaSj(B) (3eSJYQVG GdeMJhjGJ GdJGdjI (B: (3GdaUd GdChd HYfhGf JYQja GdEQTGO GdfaSj, GdaUd GdKGfj GdMGLI Edi GdEQTGO GdfaSj hVQhQJg aj eQMdI GdMVGfI, GdaUd GdKGdK GdGgJeGe HGdWad fXQI JGQjNjI, GdaUd GdQGHY CKQ GdJZjQ hGdJWhQ GdGLJeGYj Ydi GdCSQI hGfYcGSGJg Ydi GdWad(B.s
(3HHdjhLQGajI (B: (3UaMI (B152-154.s
Keywords: (3Yde faSs -- (3GdCWaGd ef (B2 (3Edi (B5 (3SfhGJs; (3GdEQTGO GdfaSjs -- (3CWaGds; (3GdUMI GdfaSjIs